Increased Hippocampus–Medial Prefrontal Cortex Resting-State Functional Connectivity and Memory Function after Tai Chi Chuan Practice in Elder Adults - Tao, Jing; Liu, Jiao; Egorova, Natalia; Chen, Xiangli; Sun, Sharon; Xue, Xiehua; Huang, Jia; Zheng, Guohua; Wang, Qin; Chen, Lidian; Kong, Jian (Frontiers in Aging Neuroscience, 2016)
Previous studies provide evidence that aging is associated with the decline of memory function and alterations in the hippocampal function, including functional connectivity to the medial prefrontal cortex (mPFC). In this study, we investigated if longitudinal (12-week) Tai Chi Chuan and Baduanjin practice can improve memory function and modulate hippocampal resting-state functional connectivity (rs-FC). Memory function measurements and resting state functional Magnetic Resonance Imaging (rs-fMRI) were applied at the beginning and the end of the experiment. The results showed that 1) the memory quotient (MQ) measured by the Wechsler Memory Scale (WMS-CR) significantly increased after Tai Chi Chuan and Baduanjin practice as compared with the control group, and no significant difference was observed in MQ between the Tai Chi Chuan and Baduanjin groups; 2）rs-FC between the bilateral hippocampus and mPFC significantly increased in the Tai Chi Chuan group compared to the control group (also in the Baduanjin group compared to the control group, albeit at a lower threshold), and no significant difference between the Tai Chi Chuan and Baduanjin groups was observed; 3) rs-FC increases between the bilateral hippocampus and mPFC were significantly associated with corresponding memory function improvement across all subjects. Similar results were observed using the left or right hippocampus as seeds. Our results suggest that both Tai Chi Chuan and Baduanjin may be effective exercises to prevent memory decline during aging.